Overcoming the Skin Permeation Barrier: Challenges and Opportunities - Vitorino, Carla; Sousa, Joao; Pais, Alberto (Current Pharmaceutical Design, 2015)
Stratum corneum (SC), the outermost layer of the skin, constitutes an excellent protective physiological barrier, and is the main challenge in transdermal drug delivery. Many approaches have been used to enhance the penetration of drugs through this layer, covering passive and active methods or the combination of both. This opens the opportunity to broaden the spectrum of drugs that can be administered through the skin, providing alternatives to existing products, and filling gaps that conventional routes failed to occupy. In this review, an overview of the different permeation enhancing methodologies is carried out, focusing on the combination of lipid nanoparticles with conventional chemical enhancers, as a proof-of-concept of a successful development strategy.
Keywords: Active methods